Language Identity of Online Business Correspondence (on Material of the French and English Languages) - N. V. Poliakova; N. A. Skitina; V. P. Shabanova (Научный диалог, 2018)
The article discusses the findings of the comparative analysis of online business correspondence in the Russian and English languages. The issue of written business discourse internationalization and identity is still unsettled, as Internet environment and attributed to it social, cultural and technological changes influence the language, regularly modifying it. The authors examined basic theories related to the study of the terms Internet communication and language identity in modern linguistic studies. The aim of the article is to identify linguistic peculiarities of expressing identity in business e-mails in modern French and English, taking into account national-cultural and sociolinguistic aspects of business communication. To achieve this goal the following research objectives were set: study the concepts of Internet communication and language identity; select and describe frequent language structures that determine the specifics of e-mails in two cultures. The findings were derived from e-mails presented both in the public domains and in foreign textbooks. In the course of the study identical vectors of development of stylistic forms of the compared languages were identified. Decrease in the degree of formality is observed in online business correspondence, which is manifested through the use of colloquial and slang expressions. Traditional opening formulas of address such as Sir and Dear are often replaced with Hello and Hi. Moreover, in English e-mails pronoun we is becoming more frequent. Nowadays, one of the trends in the development of the French language of business communication is the use of borrowings from the English language which signals about the internalization of online business correspondence.